Engineering Cupriavidus necator H16 for 3-hydroxypropionic acid production - Locker, Jessica Katie (2021)
As chemical production is largely sustained by oil-based products and accounts for 10% of the global final energy consumed, it is an essential target in the fight against climate change and ecosystem destruction. Biological synthesis in microorganisms has been proposed as the choice alternative for production of commodity chemicals using non-petroleum energy sources. Among the many chassis organisms under investigation, Cupriavidus necator displays many characteristics that make it ideal for the biosynthesis of such chemicals. Notably, the organism can grow lithoautotrophically (using only CO2 and H2 as carbon and energy sources) and on a range of non-traditional substrates.